Experimental comparison of point-of-use filters for drinking water ultrafiltration. Issue 2 (June 2017) - Totaro, M.; Valentini, P.; Casini, B.; Miccoli, M.; Costa, A.L.; Baggiani, A.
Summary: Background: Waterborne pathogens such as Pseudomonas spp. and Legionella spp. may persist in hospital water networks despite chemical disinfection. Point-of-use filtration represents a physical control measure that can be applied in high-risk areas to contain the exposure to such pathogens. New technologies have enabled an extension of filters' lifetimes and have made available faucet hollow-fibre filters for water ultrafiltration. Aim: To compare point-of-use filters applied to cold water within their period of validity. Methods: Faucet hollow-fibre filters (filter A), shower hollow-fibre filters (filter B) and faucet membrane filters (filter C) were contaminated in two different sets of tests with standard bacterial strains ( Pseudomonas aeruginosa DSM 939 and Brevundimonas diminuta ATCC 19146) and installed at points-of-use. Every day, from each faucet, 100 L of water was flushed. Before and after flushing, 250 mL of water was collected and analysed for microbiology. Findings: There was a high capacity of microbial retention from filter C; filter B released only low Brevundimonas spp. counts; filter A showed poor retention of both micro-organisms. Conclusion: Hollow-fibre filters did not show good micro-organism retention. All point-of-use filters require an appropriate maintenance of structural parameters to ensure their efficiency.